The Implementation of Digital Media-Based Project-Based Learning (PjBL) to Enhance Madrasah Ibtidaiyah Students' Critical Thinking Skills in the Society 5.0 Era - Ala Purnawati; Budiman; Neli Aprianti (Lembaga Bale Literasi, 2024)
The development of the Society 5.0 era requires the world of education to be able to integrate digital technology with a student-centered learning approach. One of the relevant learning models is Project-Based Learning (PjBL) combined with interactive digital media. This study aims to examine the effectiveness of the implementation of PjBL assisted by digital media in improving the critical thinking skills of Madrasah Ibtidaiyah (MI) students. The method used is a literature study. The results of the study show that the implementation of PjBL assisted by digital technology is able to increase student involvement, critical thinking skills, and problem-solving skills.